Persetujuan WTO Terhadap Pengabaian TRIPS Pada Saat Pandemi COVID-19 Tahun 2020-2022 - Haryadi, Rina Amelia; Tobing, Fredy B.L. (Global and Policy Journal of International Relations, 2024)
ABSTRACT The pandemic of COVID-19 has massive impact in various areas, including international trade. There was an inequality between developed and developing countries, especially in the access of vaccines. In order to reduce inequality, South Africa and India proposed The Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) waiver proposal to the World Trade Organization (WTO) in 2020. TRIPS is an instrument established by the WTO that aims to protect intellectual property rights, which can increase innovation. Regarding to the TRIPS Waiver proposal, developed countries are worried the waiver will decrease innovation and development of the pharmaceutical industry in their countries. However, amidst the pros and cons, WTO approved the waiver proposal in 2022. Using qualitative research methods, this paper will discuss WTO as an organization which regulates world trade also has a role in dealing with COVID-19, specifically in trade and access of medicine and vaccines production. Therefore, the WTO has a role in providing patent waivers, so that developing countries able to produce vaccines. WTO has three roles, such as a policy instrument by receiving aspirations from member countries, providing a discussion forum, and as an actor to make decisions that will be implemented by all WTO members. Keywords: COVID-19, WTO Roles, The Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS), World Trade Organization (WTO) ABSTRAK Pandemi COVID-19 memberikan dampak yang besar di berbagai bidang, termasuk perdagangan internasional. Terdapat ketimpangan antara negara maju dan negara berkembang, terutama dalam akses vaksin. Untuk mengurangi ketimpangan, Afrika Selatan dan India mengajukan pengabaian The Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) kepada Organisasi Perdagangan Dunia (WTO) pada tahun 2020. TRIPS merupakan instrumen yang dibentuk oleh WTO yang bertujuan untuk melindungi hak kekayaan intelektual yang dapat meningkatkan inovasi. Terkait usulan Keringanan TRIPS, negara maju khawatir pengabaian tersebut akan menurunkan inovasi dan pengembangan industri farmasi di negaranya. Namun, di tengah pro dan kontra, WTO menyetujui usulan keringanan tersebut pada tahun 2022. Dengan menggunakan metode penelitian kualitatif, makalah ini akan membahas WTO sebagai organisasi yang mengatur perdagangan dunia juga memiliki peran dalam menangani COVID-19, khususnya dalam perdagangan dan akses produksi obat-obatan dan vaksin. Oleh karena itu, WTO memiliki peran dalam memberikan keringanan paten, sehingga negara berkembang mampu memproduksi vaksin. WTO memiliki tiga peran, yaitu sebagai instrumen kebijakan dengan menampung aspirasi negara anggota, menyediakan forum diskusi, dan sebagai aktor untuk membuat keputusan yang akan dilaksanakan oleh semua anggota WTO. Kata Kunci: COVID-19, Peran WTO, The Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS), World Trade Organization (WTO)